WAWASAN KEINDONESIAAN DALAM TAFSIR AL QUR’AN AL KARIM KARYA MAHMUD YUNUS - Khairunnas Jamal (AL-FIKRA, 2017)
Tafsir Al Qur'an Al Karim by Mahmud Yunus who is one of the pioneers for the study of tafseer in Indonesian language. As a work of early interpretation, this interpretation of Mahmud Yunus has a peculiarity and gives a unique impression, both from the systematic presentation and the charge in the explorative meaning of the verses of the Qur'an. Among the interesting sides of this commentary are the efforts of the authors to accommodate the phenomena occurring in society at the time. In other words, this commentary is a form of response to the author's anxiety about the problematic common in the Indonesian public, hereinafter referred to as the insight of Indonesian-ness.